Minimnya Budaya Disiplin dan Kerja Keras dalam Bekerja Khususnya dalam Ruang Lingkup Koperasi di Indonesia pada Era Industri 4.0 - Zimly Assiddiq, Naufal (Transpublika Publisher, 2021)
The culture of discipline and hard work is very important in the lives of all of us, especially in the world of work. Because the culture of discipline and hard work plays a very important role in advancing employee welfare and improving the quality of the company. In this case the cooperative as written and explained in Law number 25 of 1992 article 3, namely promoting the welfare of members. Currently, in Indonesia there are still many people who have not made a culture of discipline and hard work as a benchmark or benchmark in carrying out their work. Like going from home to office just to fill attendance, playing truant while at work and so on. Then in cooperatives such as lack of coordination and cooperation between members and administrators so that the results of the cooperatives that are run are less than optimal and not in accordance with the target. Therefore, the purpose of writing this article is to find solutions and suggestions for the lack of a culture of discipline and hard work of Indonesian cooperatives in the industrial era 4.0.